All Days 2013
DOI: 10.2118/167142-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Salinity Study to Support Surfactant Imbibition into the Bakken Shale

Abstract: In our previous study of Bakken shale imbibition, a group of surfactant formulations were examined. These surfactants consistently altered the wetting state of Bakken cores toward water-wet, and appeared to have a substantial potential to improve oil recovery from the Bakken Formation compared to brine water alone. To advance this development, this paper investigates the optimal salinities of surfactant solutions by phase behavior and IFT studies using Bakken formation water and oil. The ultimate objective of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Oil recovery using LSW in conventional formations can exceed that obtained using produced high-salinity brines . Laboratory-scale oil recoveries from ULR cores indicate that several mechanisms may be responsible for the oil recovery observed during the immersion of oil-rich shale cores in water or LSW. Possible mechanisms of oil recovery by LSW include wettability alteration, , detachment of clays, multicomponent ion exchange, desorption of polar components from rock surfaces, formation of cracks in shale due to LSW imbibition, and osmosis …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oil recovery using LSW in conventional formations can exceed that obtained using produced high-salinity brines . Laboratory-scale oil recoveries from ULR cores indicate that several mechanisms may be responsible for the oil recovery observed during the immersion of oil-rich shale cores in water or LSW. Possible mechanisms of oil recovery by LSW include wettability alteration, , detachment of clays, multicomponent ion exchange, desorption of polar components from rock surfaces, formation of cracks in shale due to LSW imbibition, and osmosis …”
Section: Chemical Eor Using Water In Ulrsmentioning
confidence: 99%
“…A study was conducted that compared fresh water, brine with 30% TDS, and aqueous solutions of anionic, cationic, and nonionic surfactants at 0.05−2 wt % in brine or formation brine at 30 wt % TDS with either no alkaline content or a dilute alkaline concentration (0.2−0.25%) (Table 6, entry 7). 252 Water and brine results were poor. Surfactant solutions were promising, with both IFT reduction and wettability alteration deemed to be important for EOR from Bakken cores.…”
Section: Spontaneous Imbibition Experimentsmentioning
confidence: 99%
“…Mattax and Kyte (1962) first suggested a scaling group for a capillary-controlled imbibition. Later, it was proposed that oil recovery from spontaneous imbibition is affected by rock wettability (Zhou et al 1996), and a modified scaling group that accommodates various shapes was also suggested (Ma et al 1997(Ma et al , 1999Morrow and Mason 2001). These scaling models are very useful for our current spontaneous-imbibition studies.…”
Section: Introductionmentioning
confidence: 99%
“…The 2 wt. % KCl concentration was used to verify the better interaction of the displacing fluid solution with the reservoir's rock, since the reservoir water presents salinity, and this interferes with the CMC value of the surfactant by the competition of salt with the hydrophilic group of surfactants in water solubility, as well as rock wettability [10,[20][21][22][23].…”
Section: Surfactant Solutions Propertiesmentioning
confidence: 99%